Hubungan Aktivitas Fisik, Kesegaran Jasmani Dan Kadar Hemoglobin Dengan Prestasi Belajar Remaja Putri SMK Penerbangan Bina Dhirgantara Karanganyar - , Jumainah, Siti Zulaekah, A., M.Si, Wahyuni, SKM., M.Kes (2016)
Background. Factors that affect the learning achievement, i.e. internal factors consist of the physiological and psychological, and external factors consist of social and non-social. In addition, academic achievement is also influenced by physical activity, physical health and hemoglobin levels. Physical fitness is the ability of a person's body to perform daily job duties without causing significant fatigue. Physical activity can also help to improve blood and oxygen to the brain so that it can reduce stress and improve mood of children. Objective. This study aimed to determine the correlation between physical activity, physical fitness and hemoglobin levels and academic achievement in female students at Bina Dhirgantara flight vocational high school of Karanganyar. Research methods. This type of research was an observational study with Cross-sectional design. Subject retrieval technique used total sampling with the number of subjects was 43 female students. Physical activity data were obtained through recall 3x24 hours, the physical fitness data were obtained through 12 minute Cooper Test, hemoglobin level data were obtained through Cyanmethemeglobin method while data of academic achievement were obtained through students learning report. Analysis of the data used Pearson Product Moment test. Results. The result of univariat analysis showed that most of physical activities were at low category (48,8%). Meanwhile, most students had poor physical fitness (58,1%). Most of hemoglobin levels were at category of anemic (67,4%). The result of the bivariat analysis with Chi-square tests, the correlations between physical activity and academic achievement showed p=0,006, physical fitness and learning achievement showed p=0,003, and hemoglobin levels and academic achievement showed p=0,001. Conclusion. There were correlations between hemoglobin levels, physical fitness and academic achievement